Laccomimus xikrin sp. nov. and new records of other species of Laccomimus Toledo & Michat, 2015 (Coleoptera: Dytiscidae: Laccophilinae) from Brazil - Braga, Rafael Benzi; Ferreira-Jr, Nelson (Zootaxa, 2016)
The genus Laccomimus Toledo & Michat, 2015 was recently erected for small drop-shape Dytiscidae beetles commonly found in Tropical South America associated with lentic waters. In the present paper a new species, Laccomimus xikrin sp. nov., is described and illustrated. New records from Brazil are presented for Laccomimus alvarengi Toledo & Michat, 2015 from Amazonas state, L. bordoni Toledo & Michat, 2015 from São Paulo state and L. variegatus Toledo & Michat, 2015 from Pará state.